A novel line type optimization and theoretical equilibrium method analysis for common hypocycloid screw motor. Issue 6 (14th August 2021) - Fan, Peng; Kuang, Y.C.
Abstract : Purpose: The rotor in screw motor is driven to rotate by highly pressure difference of drilling fluid (DF), while rotor drives drill bit to break rocks. DF works in the volume cavity (VC) which exists between the stator and rotor (SAR), these process realizes the conversion from hydraulic energy to mechanical energy finally. In order to assure seal performance and output power reliability of VC in common hypocycloid screw motor (CHSM), it's essential to survey SAR end-face profile. Design/methodology/approach: In this article, based on the internal and external cycloid method given for SAR end-face of φ172 7/8-head LZ type CHSM, the interference among SAR is established based on the meshing model through theoretical equilibrium method (TEM). Last, the reasonable design value of SAR interference in TEM is verified with the hydraulic parameters test results. Findings: The profile optimization that top-root part of rotor end-face profiles is replaced by elliptical-circular arcs (ECA) makes the transition area of tooth-top and tooth-root connect smoother than before. The reasonable interference of SAR in TEM is almost 0.16mm~0.22mm to ensure better sealing performance. Through the hydraulic test, the interference positive fluctuation or the number of SAR head reduces increase (starting-pressure-drop) SPD while negative fluctuations by contraries. Meanwhile, DF penetration also decreases the revolution speed with the SAR interference decreases. The less SAR head revolution speed is always below the more with the constant driving power and DF hydraulic drop. Ultimately, decreasing in overall-efficiency occurs for larger fluctuation of interference or or less interference among SAR. Originality/value: The line type optimization and analysis in TEM for CHSM improves the motor seal and output performance, also has important application values simultaneously.